2023
DOI: 10.3390/membranes13010116
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Mechanically Enhanced, Suturable, Fibrous Hydrogel Membranes

Abstract: Poly(vinyl-alcohol) hydrogels have already been successfully utilised as drug carrier systems and tissue engineering scaffolds. However, lacking mechanical strength and suturability hinders any prospects for clinical and surgical applications. The objective of this work was to fabricate mechanically robust PVA membranes, which could also withstand surgical manipulation and suturing. Electrospun membranes and control hydrogels were produced with 61 kDa PVA. Using a high-speed rotating cylindrical collector, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Similar results were found for all the other scaffolds (images not depicted) and can also be found in the literature. Voniatis et al [42] observed an increase in the degree of alignment of poly(vinyl alcohol) fibers produced by electrospinning, with an increase in the rotation speed of a cylindrical collector up to 6000 rpm. From the angular distribution of the fibers in the scaffolds produced in this work at the collector rotation speed of 3500 rpm, we estimated the percentage of fibers oriented within a range of 60 degrees.…”
Section: Scaffolds Morphologymentioning
confidence: 99%
“…Similar results were found for all the other scaffolds (images not depicted) and can also be found in the literature. Voniatis et al [42] observed an increase in the degree of alignment of poly(vinyl alcohol) fibers produced by electrospinning, with an increase in the rotation speed of a cylindrical collector up to 6000 rpm. From the angular distribution of the fibers in the scaffolds produced in this work at the collector rotation speed of 3500 rpm, we estimated the percentage of fibers oriented within a range of 60 degrees.…”
Section: Scaffolds Morphologymentioning
confidence: 99%